2020
DOI: 10.3390/rs12203296
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Direct Radiative Effects over China Based on Long-Term Observations within the Sun–Sky Radiometer Observation Network (SONET)

Abstract: To investigate aerosol radiative effects, the Sun–Sky Radiometer Observation Network (SONET) has performed long-term observations of columnar atmospheric aerosol properties at 20 distributed stations around China. The aerosol direct radiative forcing (RF) and efficiency (RFE, the rate at which the atmosphere is forced per unit of aerosol optical depth) were estimated using radiative transfer model simulations based on the ground-based observations dating back to 2009. Results of multi-year monthly average RF i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The flowrates were set at 1.3 and 3 L min −1 for CEA and AE33, respectively. To get the absorption coefficient correction factor measured by AE33 due to multiple scattering, aerosol absorption at λ = 532 nm determined by CEA was used as the reference (Li, Li, et al., 2020; Li, Xiao, et al., 2020). Since multiple scattering correction factor is wavelength‐independent (Saleh et al., 2014; Zhao et al., 2020), the correction factor (2.62 for this study, Figure S2 in Supporting Information ) could be also used for other wavelengths to obtain reasonable aerosol absorptions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The flowrates were set at 1.3 and 3 L min −1 for CEA and AE33, respectively. To get the absorption coefficient correction factor measured by AE33 due to multiple scattering, aerosol absorption at λ = 532 nm determined by CEA was used as the reference (Li, Li, et al., 2020; Li, Xiao, et al., 2020). Since multiple scattering correction factor is wavelength‐independent (Saleh et al., 2014; Zhao et al., 2020), the correction factor (2.62 for this study, Figure S2 in Supporting Information ) could be also used for other wavelengths to obtain reasonable aerosol absorptions.…”
Section: Methodsmentioning
confidence: 99%
“…Remote sensing observations showed that aerosol optical depth (AOD) in TP could be 10 times lower compared with sites in eastern China (de Leeuw et al., 2018; Li, Li, et al., 2020; Li, Xiao, et al., 2020; Lu et al., 2022). Previous studies evaluated that aerosol over TP had weak impact on radiative forcing based on ground based remote sensing observation, as it was less efficient to warm the atmosphere due to the low aerosol loading (Li, Li, et al., 2020; Li, Xiao, et al., 2020). However, aerosol radiative effects over TP still have large uncertainties because of inaccurate knowledge of aerosol optical properties, especially SSA.…”
Section: Introductionmentioning
confidence: 99%
“…The LIRIC-2 code [115] is an evolution of LIRIC. Also, it includes new program modules for processing data of LRS measurements when Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) of NASA's Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) satellite measures aerosols in the vicinity of AERONET or Sun-sky radiometer Observation NETwork (SONET) [116,117] radiometric site. New program shell and modules were developed to ensure the implementation of new options for the formation and preliminary processing of input data files and to estimate the uncertainty of the retrieved aerosol parameters for the specified input data uncertainty.…”
Section: Liric Inversion Code Analysis and Datamentioning
confidence: 99%
“…Aerosol composition, concentration, and optical and physical properties are important in constraining the radiative effect of aerosols [29][30][31][32][33][34]. For example, Déandreis used a chemistry-aerosol model and found that the sulfate aerosol direct radiative effect increases almost linearly as the aerosol concentration increases [29].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Déandreis used a chemistry-aerosol model and found that the sulfate aerosol direct radiative effect increases almost linearly as the aerosol concentration increases [29]. The aerosol radiative forcing at the bottom and the top of the atmosphere over China were obtained based on the long-term observations within SONET [30]. It is determined that the aerosol radiative forcing at the top of the atmosphere and the surface both doubled during an aerosol event with a peak AOD of 0.6 in Central Europe [31].…”
Section: Introductionmentioning
confidence: 99%